nusA amber mutation that causes temperature-sensitive growth of Escherichia coli. - Tsugawa, A (1988)
The nusA134 mutation was isolated from a sup0 strain as a temperature-sensitive mutant which grew at 32 degrees C but not at 42 degrees C. Immunoblot analysis showed that this mutant produced a 31,000-dalton nusA-encoded protein instead of the full-size 54,500-dalton product. Sequence and genetic analyses of the mutant nusA gene revealed a substitution of T for C at the PstI site (i.e., CTGCAG to CTGTAG), thereby creating a nonsense UAG codon. These results indicate that nusA134 is an amber mutation and that the 31,000-dalton amber fragment is active for Escherichia coli growth at 32 degrees C but not at 42 degrees C. Most lambda bacteriophage variants tested grew normally on the nusA134 mutant both at permissive and at nonpermissive temperatures. However, lambda r32, which carries an IS2 insertion beyond the tR1 terminator, was restricted at 42 degrees C. Defects in the transcriptional antitermination process, but not in transcription termination, were observed. A comparative study of nusA134 protein and a PstI-truncated protein suggests that truncation of the peptide chain at the PstI site by the amber mutation, rather than the loss of the glutamine residue, is primarily responsible for the defect in antitermination. The mode of the involvement of mutant nusA proteins in the N-mediated antitermination reaction is discussed.